Determination of CCL2 / MCP-1 levels in the serum of children with melanocytic nevus in the postoperative period after using different methods of surgical treatment - Pasichnyk, Oleh; Konoplitskyi, Viktor; Korobko, Yurii; Babina, Yuliana; Dmyrtriiev, Dmytro; Nazarchuk, Oleksandr (Acta Biomedica Atenei Parmensis, 2022)
To date, there are many methods and ways to remove pigmented skin tumors, which have their own indications and contraindications for use, early or late complications.The aim of the study was to determine the level of CCL2 / MCP-1 in the serum of patients with melanocyte skin nevi in the postoperative period with different methods of their removal.Materials and methods of research. The study involved 60 children with melanocyte skin nevi of different localization, who were hospitalized in the pediatric surgery clinic in the period from 2018 to 2020. All patients were divided into 3 groups : I group - the excision of the formation took place with a scalpel, group II - excision of the formation was performed using a high-intensity surgical laser, group III - excision of the formation using a high-frequency electrosurgical device "BOWA-ARC 350.Results and discussion. The results of studies showed an increase in the level of CCL2 / MCP-1 in the plasma of patients of group I in 2,6 times 12 hours after surgery and 3,15 times in 24 hours after surgery. A similar dynamics of increase in the level of CCL2 / MCP-1 in plasma was observed in patients of group II, but was more pronounced. The largest increase in CCL2 / MCP-1 levels was in comparison group III.Conclusions. High levels of CCL2 / MCP-1 in the plasma of patients of groups II and III 12 and 24 hours after surgery convincingly indicate the presence of a pronounced inflammatory reaction under the influence of thermal damaging factor on skin tissues.